Pengaruh Financing to Deposit Ratio dan Total Asset Turn Over terhadap Non Performing Financing di BTN Syariah Periode 2019-2023 - Arumsari, Azmi; Rakhman, Faisal (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
The background of this research is that are fluctuations in values FDR, TATO and NPFas well discrepancies between the theory of the relationship between FDR and TATO to NPF in several quarters. This study aims to find out how the influence of FDR and TATO on NPF at BTN Sharia Bank for the 2019-2023 period, both partially and simultaneously. The type of research is associative quantitative, secondary data types, The sample in this study is BTN Sharia Bank quarterly financial reports for the 2019-2023 period. The research result show that there is a significant influence between FDR on NPF with the results of the t test where the value of tcount > ttable (6,3681 > 1,734) and the contribution of FDR to NPF is 69.26% from the R2 test results, there is a significant influence between TATO and the t test results where tcount > ttable (2,8610 > 1,734) and TATO contribution to NPF is 31.26% from the results of the R2 test. Simultaneously there is a significant influence between FDR and TATO on NPF at BTN Sharia Bank for the 2019-2023 period with the F test results where the value of count > F table (7,84 > 3,59) and the contribution of FDR and TATO to NPF simultaneously is equal to 69.27% of the R2 test results.